(3eHGQb GdCRgGQ aj TQM eTGQb GdCfhGQs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc , (B801 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi gOjI GdgOGjI jbhd GdVYja YHO GddWja Hf YHO GdYRjR GdeYQha heeG Ufa ajg ef GdcJH GdaGNQI GdhGaQI eTGQb GdCfhGQ hcGfJ dg TQhM hCSJNjQ Gddg aj jhej haj CeSj Cf CTQMg TQMG jNHQ Yf NHGjG YHGQGJg s
(3BNQgG (B:s
(3Qhi eSde Yfg (B[ (3dHjc YeQG (B( (3cPG (B) (3hMLG efUhH ebOQ Cj eQjOG YeQI Ch (B[] (3GdNGaV Cj HYeQI gPG jOd Ydi Cfg cGf bGQfG JbOe GdcdGe heG gh CUM GdQhGjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 59s
(3eYLe GdeDdajf (B2 / 215s
(3cTa GdXfhf (B2 / 1689s
(3TPQGJ GdPgH (B7 / 342s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs